2021
DOI: 10.1016/j.jgr.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin facilitates brain delivery of donepezil, a therapeutic drug for Alzheimer disease, through lysophosphatidic acid 1/3 and vascular endothelial growth factor receptors

Abstract: Background Gintonin is a ginseng-derived exogenous G-protein–coupled lysophosphatidic acid (LPA) receptor ligand, which exhibits in vitro and in vivo functions against Alzheimer disease (AD) through lysophosphatidic acid 1/3 receptors. A recent study demonstrated that systemic treatment with gintonin enhances paracellular permeability of the blood–brain barrier (BBB) through the LPA1/3 receptor. However, little is known about whether gintonin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have demonstrated the effect of gintonin on the BBB permeability based on the in vitro or the in vivo models [ 16 18 24 25 ]. In a study using human brain microvascular endothelial cells, gintonin induced widening of the junctional spaces, modulated the expression levels of the endothelial junctional proteins such as cadherin, occludin, zonula occludens 1, and claudin-5, and also enabled the entrance of large molecules to enter the cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated the effect of gintonin on the BBB permeability based on the in vitro or the in vivo models [ 16 18 24 25 ]. In a study using human brain microvascular endothelial cells, gintonin induced widening of the junctional spaces, modulated the expression levels of the endothelial junctional proteins such as cadherin, occludin, zonula occludens 1, and claudin-5, and also enabled the entrance of large molecules to enter the cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using human brain microvascular endothelial cells, gintonin induced widening of the junctional spaces, modulated the expression levels of the endothelial junctional proteins such as cadherin, occludin, zonula occludens 1, and claudin-5, and also enabled the entrance of large molecules to enter the cells [ 24 ]. In a rodent model, the fluorescent-labeled gintonin well distributed throughout the endothelium, neurons and glial cells after intravenous injection [ 18 ]. It is also found that the permeability enhancing effect of gintonin is mediated by its binding with the highly expressed LPA receptors in the cerebrovascular endothelium, the LPA 1/3, and secondary increment of VEGF [ 16 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations